2022
DOI: 10.1002/ejoc.202200348
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Angucycline/Tetrangulol Derivatives Using Suzuki‐Miyaura Cross‐Coupling and Ring‐Closing Carbonyl‐Olefin Metathesis Reactions

Abstract: Key steps in the synthesis of derivatives of the angucycline, tetrangulol include the use of a palladium catalyzed Suzuki-Miyaura cross-coupling reaction for the assembly of 2-(1,4dimethoxy-3-(2-methylprop-1-en-1-yl)naphthalen-2-yl)-3-methoxy-5-methylbenzaldehyde from 2-iodo-3-methoxy-5-methylbenzaldehyde and 2-(1,4-dimethoxy-3-(2-methylprop-1-en-1yl)naphthalen-2-yl)-4,4,5,5-tetramethyl-1,3,2-dioxaborolane. The biaryl product was then subjected to an iron-catalyzed ring-closing carbonyl-olefin metathesis react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…We then found that the reduction of aldehyde 9 provided a benzyl alcohol directing group that allowed for reproducible ortho -lithiation and trapping by I 2 [trapping with B­(OEt) 3 under these conditions resulted in no reaction]. , Oxidation with PCC afforded iodinated aldehyde 10 in 55% yield over 3 steps, needing only one chromatographic purification of the final product. The 3-step sequence proved reproducible over multiple trials and was scalable.…”
Section: Results and Discussionmentioning
confidence: 99%
“…We then found that the reduction of aldehyde 9 provided a benzyl alcohol directing group that allowed for reproducible ortho -lithiation and trapping by I 2 [trapping with B­(OEt) 3 under these conditions resulted in no reaction]. , Oxidation with PCC afforded iodinated aldehyde 10 in 55% yield over 3 steps, needing only one chromatographic purification of the final product. The 3-step sequence proved reproducible over multiple trials and was scalable.…”
Section: Results and Discussionmentioning
confidence: 99%